Diabetes Insipidus in Severe Traumatic Brain Injury Patient: A Case Report - Zaelany, Allief Ilman; Fatoni, Arie Zainul (Journal of Anaesthesia and Pain, 2025)
Background: Traumatic brain injury (TBI) contributes to significant morbidity and mortality. It leads to neuronal and vascular damage that can disrupt the function of the hypothalamus and pituitary gland, sometimes resulting in diabetes insipidus (DI). This study aims to examine DI as a complication of severe TBI and seeks to emphasize the importance of appropriate diagnosis, intervention, and monitoring to reduce the risk of mortality from TBI with DI. Case: We present a case of a severe TBI patient who had a traffic accident, resulting in subdural hematoma (SDH), subarachnoid hemorrhage (SAH), and ala magna fracture of the sphenoid bone. On the fourth day of treatment (the second day in the ICU), the patient experienced DI, characterized by a urine output rate of 4.2 cm3/kg/hour and hypernatremia (147 mmol/l). The patient was treated with fluid resuscitation and desmopressin. Symptoms improved after eight days of treatment, characterized by a urine output rate of 2.8 cm³/kg/hour and a serum sodium level of 159 mmol/l. This showed significant clinical improvement. On the tenth day, urine output returned to normal, with a lower serum osmolality, and the patient was discharged from the hospital. Conclusion: DI, as a severe complication of TBI, has the potential to increase mortality. This case underscores the importance of early detection, appropriate treatment, and ongoing monitoring to improve prognosis and reduce the risk of death associated with DI after traumatic brain injury (TBI).